Perbandingan Algoritma Golomb Rice Dan Interpolative Coding Dalam Mengkompresi File Video - Refo Irfansyah (STMIK Budi Darma, 2022)
Compression is a technique to reduce the amount of data size from the original data. The general principle used in the video compression process is to reduce the duplication of data in the video so that less memory is needed to represent the video. The size of the video file is quite large so that it requires a large enough storage and video files with a long duration greatly affect the storage space and delivery time which is long enough so that data compression is needed. In this study, a comparison of algorithms was carried out to find out which algorithm was effective in the MP4 file compression process. The algorithms that will be compared are the Golomb Rice Algorithm and Interpolative Coding. Both algorithms are algorithms for the compression process. The comparison variables between the two algorithms are Ratio Compression (Rc), Compression Ratio (Cr), Redundancy (Rd) and Space Saving (Ss). The expected result in this study is to obtain a compressed file that is smaller in size, so that the results can be compared. which algorithm is more effective in compressing video files.